Interface Thermal Resistance And Thermal Conductivity Of Polymer Composites At Different Types, Shapes, And Sizes Of Fillers: A Review - Omar, Ghazali; Masripan, Nor Azmmi; A. Hamid, Husna; Che Othaman, Siti Syahirah; Jasmee, Solehah (Wiley Online Library, 2021)
The growing demand toward miniaturization and power device packaging required new die-attach materials with high thermal conductivity (TC). Multitudinous attention is being paid to enhance the TC of thermally conductive polymer composites as it is easy to fabricate and environmentally friendly and has low-cost processability. However, after years of extensive research, it can be concluded that reinforcing different morphologies of fillers (types, sizes, and shapes) into polymer composite creates interfacial thermal resistance (ITR) that greatly constrains the TC value. Thus, this article presents an exhaustive review in minimizing the ITR effect by optimizing the types, sizes, and shapes of the fillers used. This literature also seeks to review the use of different morphologies of fillers in single and hybrid polymer composites. It was found that hybridizing two different fillers shows remarkable TC enhancement due to its synergistic effect and formation of three-dimensional network/conduction path. The size and shape of fillers used play a vital role in improving the TC of the polymer composite compared with the type of filler used due to more contact area created, which significantly reduces the ITR. The results presented here may facilitate improvement in the development of future work for new die attach of the thermally conductive polymer composite.